ZnO-SnO2 binary oxide nanocomposite photodiode and photonic applications - Yalcin, Mesut; Dere, Aysegul; Yakuphanoğlu, Fahrettin (Elsevier, 2024)
In this study, Al/p-Si/ZnO-SnO2/Al was created by fabricating a binary oxide nanocomposite photodiode device. The electrical properties of the fabricated photodiode were investigated by current-voltage and capacitance-voltage measurements. The ideality factors, barrier heights, and series resistance values of the photodiode were calculated comparatively using current-voltage characteristics as well as the Cheung-Cheung and Norde methods. The ideality factor values were calculated in the ranges of 4.16-6.07 and 2.14-5.46 for the I-V and Cheung-Cheung methods, respectively. The barrier height was calculated in the ranges of 0.17-0.19 from I-V, 0.42-0.72 for the Cheung-Cheung method, and 0.57-0.61from the Norde method. The lowest series resistance values were calculated as 2658 omega according to Cheung and 38.74 omega according to Norde. The detector properties of the photodiode were analyzed by calculating the responsivity (R) and detectivity (D*) values. The highest R and D* values were calculated as 3069 mA/W and 2.36x1011 Jones, respectively.
Keywords: Binary oxide nanocomposite; Ideality factor; Photodiode; Detectivity; Responsivity